ANALISIS KADAR PROTEIN IKAN DEPIK (Rasbora tawarensis) DI DANAU LAUT TAWAR KABUPATEN ACEH TENGAH (Protein Content Analysis of Depik (Rasbora tawarensis) In Laut Tawar Lake Aceh Tengah) - Iskandar Munthe; Muhammad Isa; Winaruddin Winaruddin; Sulasmi Sulasmi; Herrialfian Herrialfian; Rusli Rusli (Universitas Syiah Kuala, 2016)
This study aimed to determine protein content of depik (Rasbora tawarensis) fish collected from fish culture in Laut Tawar Lake, Aceh Tengah. Protein content in fish was analyzed using Kjehdal method with two replications. The result showed that average protein content of depik fish was 15.29%. Based on the result, it could be concluded that protein content of fish depik from Laut Tawar Lake is 15.29%.